Biopolymer and green energy from palm oil mill effluent using bioelectrochemical system - Khan, Maksudur R.; M. Amirul, Islam; Ong, Huei Ruey; Cheng, C. K.; Hamidah, Abdullah; Mior Ahmad Khushairi, Mohd Zahari (2018)
Polyhydroxybutyrates (PHB) are bio-plastics that are produced by selective microbial species utilizing carbon rich substrates. Anode of microbial fuel cell (MFC) is considered as bioreactor to produce biopolymer from MFC system. In Malaysia, palm oil mill effluent (POME) is one of the major wastewater which possesses very high BOD and COD. Each ton of crude palm oil produces 5-6 tons of Palm oil mill effluent (POME) and existing POME treatment is highly energy intensive. The present invention is focused on the production of PHB in MFC from POME using controlled inoculum.